Leukoaraiosis and collateral blood flow in stroke patients with anterior circulation large vessel occlusion. (20th January 2020) - Mark, Ian; Seyedsaadat, Seyed Mohammad; Benson, John C; Kallmes, David F; Rabinstein, Alejandro A; Brinjikji, Waleed
Abstract : Background: Leukoaraiosis and collateral blood flow are processes that involve small vessels, the former related to flow within the deep perforating arterioles and the latter involving the small, cortical pial-pial connections, both of which are independently used to predict cerebrovascular events and treatment outcomes. The aim of this study was to investigate their relationship to each other. Methods: We retrospectively reviewed patients who underwent mechanical thrombectomy for stroke with pre-procedural CT imaging within 24 hours of the onset of symptoms. Leukoaraiosis was graded by the total Fazekas score on non-contrast CT, periventricular white matter (PVWM) and deep white matter (DWM) scores, both ranging from 0 to 3. Collateral cerebral blood flow was measured by the American Society of Interventional and Therapeutic Radiology/Society of Interventional Radiology (ASITN/SIR) collateral scale. Results: 178 patients were included with a mean age of 67.6±14.8 years. We found an inverse relationship between total Fazekas score and collateral flow (p<0.0001). Among patients with good collaterals, 75.1% had total Fazekas scores of 0–2, compared with 36.6% of patients with moderate collaterals and 32.7% of patients with poor collaterals with total Fazekas scores of 0–2. Mean Fazekas scores were 1.6±1.5, 3.1±1.5 and 3.4±1.6 for good, moderate and poor collaterals, respectively (p<0.0001). On multivariate analysis, total Fazekas score was the only variable independently associated with collateral status (p<0.0001). Conclusions: Increasing severity of leukoaraiosis is associated with poor collateral grade among ischemic stroke patients with anterior circulation large vessel occlusion. These findings suggest that leukoaraiosis may be a marker for global cerebrovascular dysfunction.